2016
DOI: 10.3389/fmars.2016.00142
|View full text |Cite
|
Sign up to set email alerts
|

Does the Seal Licensing System in Scotland Have a Negative Impact on Seal Welfare?

Abstract: This study examined the licensing system that permits seal shooting in Scotland, which was established under Part 6 Conservation of Seals of the Marine (Scotland) Act 2010. Four approaches were used: data were collated and analyzed from both the Scottish Government and Scottish Marine Animal Stranding Scheme; a survey was sent to current license holders and informal interviews were conducted with key stakeholder types. Between February 2011 and the end of October 2015, 1229 gray seals, and 275 common seals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In the water, it is far harder to assess whether a shot seal has been wounded or whether it has been killed instantly. There have been cases of seals in Scotland not being killed by the first shot [41]. The EFSA Risk Assessment found that it is "very likely to likely" that shooting seals is an effective way to kill them and that suffering would be "negligible, especially if death was ensured by another method of killing" [30].…”
Section: Woundingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the water, it is far harder to assess whether a shot seal has been wounded or whether it has been killed instantly. There have been cases of seals in Scotland not being killed by the first shot [41]. The EFSA Risk Assessment found that it is "very likely to likely" that shooting seals is an effective way to kill them and that suffering would be "negligible, especially if death was ensured by another method of killing" [30].…”
Section: Woundingmentioning
confidence: 99%
“…The authors of the EFSA report concluded that when seals are shot in locations where reaching the shot animal was difficult (e.g., in open deep water) then there was an unknown risk of causing unavoidable pain, distress and suffering [30]. As seals shot in management situations are rarely checked or the carcasses recovered then this may be a significant source of animal suffering in some fisheries/around some fish farms [41]. Nunny, Simmonds, and Butterworth report that there is no international standard for how seals should be shot and, therefore, it is possible that seals are being shot in circumstances that lead to suffering [3].…”
Section: Woundingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Code does not address how to check the state of consciousness of a shot seal nor does it specify what a "rapid death" is in terms of time to death. Nunny et al(2016) reported that some seals shot in Scotland did not die immediately.…”
Section: How Seals Are Killedmentioning
confidence: 99%